2007
DOI: 10.1200/jco.2006.10.2699
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Randomized Clinical Trial Results in the National Comprehensive Cancer Network on the Use of Tamoxifen After Breast Surgery for Ductal Carcinoma in Situ

Abstract: Tamoxifen use after surgery for DCIS at NCCN centers increased after presentation of the B-24 results. Rates varied substantially by institution, suggesting that physicians differ in how they weigh the modest reduction in breast cancer risk with tamoxifen against its potential adverse effects in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 17 publications
3
29
2
Order By: Relevance
“…Previous work reported that the use of tamoxifen reduces the 5-year rate of ipsilateral and contralateral BC in patients with DCIS; factors predicting tamoxifen use in their study were breast-conserving surgery and younger age 24. Consistent with their conclusion, our study showed that patients who took tamoxifen were less likely to elect CPM than those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work reported that the use of tamoxifen reduces the 5-year rate of ipsilateral and contralateral BC in patients with DCIS; factors predicting tamoxifen use in their study were breast-conserving surgery and younger age 24. Consistent with their conclusion, our study showed that patients who took tamoxifen were less likely to elect CPM than those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…Still, it is likely the treatment prescribed by an oncologist can be influenced by many different factors. Tamoxifen use after surgery for ductal carcinoma in situ increased after presentation of the NSABP B-24 results [16]. Rates varied substantially by institution, suggesting that physicians differ in how they weigh the benefit against the potential adverse effects.…”
Section: Discussionmentioning
confidence: 95%
“…However, wide practice variation in recommendations for use and uptake of these therapies for DCIS suggests that communication with physicians can exert a strong influence on whether or not patients use these medications. 1,13,18,19 This study identified several patient, tumor, treatment, and physician-patient communication-related factors associated with the discussion, use, and discontinuation of adjuvant HT in a demographically and ethnically diverse sample of women.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,[14][15][16][17] As a result, there is a lack of consistency in both the recommendations for and uptake of tamoxifen use in the setting of DCIS. 1,18,19 The NSABP B35 trial is currently underway to compare the effectiveness of anastrazole (an aromatase inhibitor) to that of tamoxifen in postmenopausal women with hormone receptor-positive DCIS. 11,20 Previous research into factors associated with use of adjuvant HT has focused on women with invasive breast cancer, where its use has been more consistently recommended as standard of care.…”
Section: Introductionmentioning
confidence: 99%